Restauração da mata atlântica no vale do Rio Paraíba do Sul, RJ: buscando estratégias sustentáveis - Siqueira, Flávia Freire de (2015)
Techniques of forest restoration have been improved in orderto lead the restored area to a state close to the initial condition, recovering the biological integrity of the system. A few studied areas had an evaluation of their success compared to reference forest areas and, in most cases, whether successful, results are non-published. Such techniques have been used by Furnas Company in the region named Vale do Paraíba within Rio Paraíba do Sul watershed, in an area of Atlantic Forest, southeastern Brazil. The company showed interest to evaluate the success of restoration projects surrounding Usina Hidrelétrica do Funil (UHE – Funil), aiming the improvement of restoration strategies. For this evaluation, it was established a partnership with Universidade Federal de Lavras (University of Lavras). Therefore, the present research arose, aimed to evaluate whether four restoration areas are achieving reference standards found in semideciduous seasonal forest fragments. The characteristics of the plant community as well as plots were measured in ten areas, four restoration plantings IB (14 years), CG (15 years), and FUR (20 years), and six reference areas of semideciduous seasonal forest in different successional stages INI (10 to 16 years), INT (30 to 40 years), and ADV (over 60 years), two fragments per stage. Environmental variables of plant community and plots were measured, i.e., floristic and structural composition of the community, environmental groups, dispersion syndrome, liana abundance, exotic species abundance, regeneration presence, edaphic, microclimate, and landscape characteristics, soil surface covering, slope and canopy openness. Plantings presented decreased richness, lesser percentage of pioneer and zoochoric individuals, as well as greater canopy covering when compared to reference areas. Plantings had significant lower richness in comparison to reference areas, also strongly differing regarding species composition. Microclimate, soil fertility, and soil surface covering were similar between plantings and reference areas. There was a high percentage of exotic individuals in plantings and a small colonization of individuals after implementing restoration projects. The four plantings were similar regarding richness and number of saplings. The percentage of zoochoric individuals influenced positively and the slope influenced negatively the abundance of plots. The oldest planting (FUR) differed to the most from the forest areas in several parameters evaluated. CB planting was the most similar, and it obtained different cultivation treatment such as replanting, weed control, and larger fertilization. Besides, a smaller percentage of pioneer and exotic individuals were used in this planting. Results showed that restoration plantings do not seem to be prospering in a natural and self-sustainable successional process towards the parameters observed in forest areas. Results also showed that there is the need to change the strategies adopted, favoring the planting of native species from different successional groups as well as a higher number of zoochoric species. In addition, cultivation treatment may favor a better development of plantings.